EFFECT OF DIFFERENT SPEED OF TWO PLOWS TYPES ON SOME MAGHINARY UNIT PERFORMANCE INDICATORS - Z. Amer, K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This experiment was conducted to evaluate stadying the effect of different speed of two plows types on some machinary unit performance indicators. New Holland TD80 was used in this study.Three  machinery speeds included; 2.72,4.34 and 6.23 km.hr-1 which represent  main plot and two plows included; moldboard plow and disk plow which represent sub plot were used in this study. slippage percentage, practical productivity, Field efficiency, soil volume disturbs and fuel consumption were measured in this experiment Split plot design.The results can be summarized as Fallow; The 6.26 km.hr-1   speed  gave  higher  practical  productivity  0.31  ha.hr-1, higher  soil  volume  disturbs  599.07 m3.hr-1,lowest fuel consumption 30.69 L.hr-1 and higher Field efficiency 60.89%. While speed 2.72 km.hr-1 gave lowest slippage percentage 8.69%.The moldboard plow on  the disk plow gave lowest slippage percentage 9.48%, higher  practical productivity 0.26 ha.hr-1, higher soil volume disturbs 514.89 m3.hr-1, higher Field efficiency 58.98% and lowest fuel consumption 33.77 L.hr-1. As for the significant of overlap between the speed 6.23 km.hr-1 and the moldboard plow it has impacted significantly in all traits.